Cultural Mentors: Using Transformative Learning Theory to Examine Adaptation and Supporting Relationships of Women Educators in Cross-Cultural Settings - Carol R. Lyon (Adult Education Research Conference, 2000)
The purpose of the roundtable is to discuss a qualitative study-in-progress, which examines how women educators who have worked abroad for six months or more view the role of supporting relationships in facilitating transformative learning.